Activity-based protein profiling reveals off-target proteins of the FAAH inhibitor BIA 10-2474 - van Esbroeck, Annelot C M; Janssen, Antonius P A; Cognetta, 3rd, Armand B; Ogasawara, Daisuke; Shpak, Guy; van der Kroeg, Mark; Kantae, Vasudev; Baggelaar, Marc P; de Vrij, Femke M S; Deng, Hui; Allarà, Marco; Fezza, Filomena; et al. (Science (American Association for the Advancement of Science), 2017)
A recent phase 1 trial of the fatty acid amide hydrolase (FAAH) inhibitor BIA 10-2474 led to the death of one volunteer and produced mild-to-severe neurological symptoms in four others. Although the cause of the clinical neurotoxicity is unknown, it has been postulated, given the clinical safety profile of other tested FAAH inhibitors, that off-target activities of BIA 10-2474 may have played a role. Here we use activity-based proteomic methods to determine the protein interaction landscape of BIA 10-2474 in human cells and tissues. This analysis revealed that the drug inhibits several lipases that are not targeted by PF04457845, a highly selective and clinically tested FAAH inhibitor. BIA 10-2474, but not PF04457845, produced substantial alterations in lipid networks in human cortical neurons, suggesting that promiscuous lipase inhibitors have the potential to cause metabolic dysregulation in the nervous system.